Effect of Two Interventions on Sleep Quality for Adolescent and Young Adult Cancer Survivors: A Pilot Randomized Controlled Trial. Issue 2 (21st March 2022) - Li, Lijun; Wang, Lu; Sun, Qian; Xiao, Panpan; Duan, Yinglong; Liu, Xiangyu; Zhou, Jianda; Xie, Jianfei; Cheng, Andy S. K.
Abstract : Background: Sleep disturbance is common among adolescent and young adult (AYA) cancer survivors. Physical activity (PA) and behavioral activation (BA) therapy have been reported as enhancing sleep quality, but few studies exist on the effects of such interventions combined with technology to promote sleep quality in AYA cancer patients. Objective: The aim of this study was to investigate the feasibility and effects of intelligent wearable device–based PA therapy and internet-based modified BA therapy to improve sleep quality among AYA cancer patients. Methods: A randomized controlled trial with 143 AYA cancer patients was conducted. Participants were randomly assigned to a control group (n = 48), which performed routine care, a PA group (n = 47), which received 8-week PA therapy based on intelligent wearable devices, and a BA group (n = 48), which participated in internet-based modified BA therapy for 8 weeks. Results: At 1 week and 3 months after the intervention for sleep quality, there were statistically significant differences between the PA group and the control group ( P = .020), but no statistically significant difference between the BA group and the control group. Conclusions: The intelligent wearable device–based PA therapy has more advantages than internet-based modified BA therapy in improving the overall state of AYA cancer patients, and the intervention effect was sustained for at least 3 months. Implications for Practice: Developing and implementing PA plans for AYA cancer survivors can improve their sleep quality. Social media, intelligent wearable devices, and mobile health applications have unique advantages in promoting sleep quality for AYA cancer survivors.